Research on integrated safety assessment model of electric vehicle charging process. Issue 1 (25th May 2022) - Sun, Lei; Ma, Yong; Li, Xiaohan; Guo, Dongliang; Liu, Jianjun; Wu, Peng; Xiao, Peng
Abstract: With the rapid development of electric vehicles (EV), the problem of charging safety is a multifaceted and complex issue. Taking the integration of electric vehicle charging as the research object, including power batteries, charging piles, and power distribution grids, charging data is collected based on data mining technology. At the same time, the factors affecting charging safety are analysed, and an integrated index set is established and optimised. The comprehensive fuzzy evaluation method is used to comprehensively analyse the monitoring data of the electric vehicle charging process, the weight is determined based on the grey correlation method and the expert scoring mechanism, and an integrated evaluation model of the electric vehicle charging process is established. Analyse five sets of charging data in Nanjing through calculation examples, and output the integrated health degree of the electric vehicle charging process so that the equipment can be maintained in a targeted manner, which effectively proves the practicability and reliability of the assessment model.